Poor adherence to the option B+ care and associated factors for the prevention of mother-to-child transmission among pregnant and lactating mothers attending ART clinics of Southwestern Ethiopia: A facility based cross-sectional study - Nuredin Mohammed Guta; Miresa Guteta; Ashanafi Asefa; Sisay Tulu; Biruk Bogale; Gachana Midaksa; Abinet Abebe (Elsevier, 2024)
Introduction: Globally, over 90 % of newborns' HIV infections occur through mother-to-child transmission. However, only 50 % of pregnant women living with HIV received effective antiretroviral regimens. So, this study aimed to assess poor adherence to option B+ care and associated factors for the prevention of mother-to-child transmission among pregnant and lactating mothers attending ART clinics in Southwestern Ethiopia. Methods and materials: An institution-based cross-sectional study was conducted with a sample of 284 HIV+ pregnant and lactating mothers who were on the PMTCT follow-up in ART clinics in southwest Ethiopia. The data were entered using EPI Data Version 3.1 and exported to SPSS Version 25 for further analysis. Binary logistic regression models were employed to identify associated factors for poor adherence to option B+ care of PMTCT using AOR with the corresponding 95 % CI. Result: The level of poor adherence to option B+ care in PMTCT was 12.6 %. The study showed that disclosure status [AOR: 0.16 [95 % CI; 0.05, 0.49]], forgetfulness [AOR = 10.5; 95 % CI [3.8, 29.5]], fear of drug side effects [AOR: 3.97 [95 % CI: [1.1, 10.4]], and fear of stigma and discrimination [AOR: 6.7, 95 % CI: [2.5, 17.7]] were significantly associated with adherence to option B+ care. Conclusions: The prevalence of poor adherence to option B+ care in this study was high. Fear of drug side effects, fear of stigma and discrimination, forgetfulness, and disclosure status were factors significantly associated with adherence to option B+ care. Proper counseling and awareness creation on drug adherence were strongly recommended.